Endoscopic ultrasound in the diagnosis of cholangiocarcinoma as the etiology of biliary strictures: a systematic review and meta-analysis - Navaneethan, Udayakumar (Gastroenterol Rep (Oxf), 2015)
Background and aim: Extrahepatic cholangiocarcinoma (CCA) typically presents as biliary strictures. Endoscopic ultrasound (EUS)-fine needle aspiration (FNA) may contribute to the diagnosis of CCA as the etiology of extrahepatic biliary strictures. Our aim was to study the uselfulness of EUS-FNA in diagnosing CCA as the etiology of biliary strictures. Patients and methods: In this meta-analysis, PUBMED and EMBASE databases were examined to find studies published to April 2014 where diagnostic correlation of CCA was available. Studies reporting only “positive for malignancy” were included in our analysis. The main outcome measurements were sensitivity, specificity and likelihood ratio. Results: Six studies were included, covering 196 patients. The overall pooled sensitivity and negative likelihood ratio (LR-) of EUS-FNA for diagnosis of CCA were 66% [95% confidence interval (CI) 57–74%] and 0.34 (95% CI 0.26–0.43), respectively. In five studies (146 patients), where a mass lesion was detected during EUS, the pooled sensitivity and LR- of EUS-FNA for diagnosis of CCA were 80% [95% CI 72–87%] and 0.20 (95% CI 0.13–0.28), respectively. In the 49 patients with a negative brush cytology, the pooled sensitivity and LR- of EUS-FNA for diagnosis of CCA were 59% [95% CI 44–73%] and 0.41 (95% CI 0.27–0.56), respectively. Conclusions: Our study suggests that EUS-FNA is useful in the evaluation of CCA as the etiology of biliary strictures. EUS-FNA may improve the diagnosis of CCA in patients with negative cytology and no mass on cross-sectional imaging.